Sense and Meaning of the Global Citizenship and development education. A diagnosis of teachers’ perceptions and current challenges in educational centers in the province of Zaragoza - Comá-Roselló, Teresa; BLASCO-SERRANO, Ana Cristina; DIESTE, Belén (Iberoamerican Journal of Development Studies, 2020)
Global Citizenship Education (GCE) is committed to a global vision of the world, enhancing the critical sense and social commitment. In this paper, it is aimed to analyze how teachers of Primary and Secondary Education in the province of Zaragoza understand the ECG. In the paper, it is also pretend to reflect about the motivations to carrying out actions of this type in educational centers. In the non-experimental descriptive study, it is showed the data obtained through a survey completed by 77 centers. Teachers consider it relevant to work on Education for Global Citizenship in a transversal way. Their education model focus on a comprehensive education of people, social responsibility and active participation. The development of ECG proposals related to improvements in teacher training, methodology and relationship with the educational community, external agents and educational administration is considered a future challenge.
Keywords: Education for Development; Global Citizenship; Participation; Teacher Training